High-Resolution Measurement of Local Activation Time Differences From Bipolar Electrogram Amplitude - Gaeta, Stephen; Bahnson, Tristram D.; Henriquez, Craig (Frontiers in Physiology, 2021)
Localized changes in myocardial conduction velocity (CV) are pro-arrhythmic, but high-resolution mapping of local CV is not yet possible during clinical electrophysiology procedures. This is in part because measurement of local CV at small spatial scales (1mm) requires accurate annotation of local activation time (LAT) differences with very high temporal resolution (<=1ms), beyond that of standard clinical methods. We sought to develop a method for high-resolution measurement of LAT differences and validate against existing techniques. First, we use a simplified theoretical model to identify a quantitative relationship between the LAT difference of a pair of electrodes and the peak amplitude of the bipolar EGM measured between them. This allows LAT differences to be calculated from bipolar EGM peak amplitude, by a novel “Determination of EGM Latencies by Transformation of Amplitude” (DELTA) method. Next, we use simulated EGMs from a computational model to validate this method. With 1kHz sampling, LAT differences less than 4ms were more accurately measured with DELTA than by standard LAT annotation (mean error 3.8% vs 22.9%). In a 1-dimensional and a 2-dimensional model, CV calculations were more accurate using LAT differences found by the DELTA method than by standard LAT annotation (by unipolar dV/dt timing). DELTA-derived LAT differences were more accurate than standard LAT annotation in simulated complex fractionated EGMs from a model incorporating fibrosis. Finally, we validated the DELTA method in vivo using 18,740 bipolar EGMs recorded from the left atrium of 10 atrial fibrillation patients undergoing catheter ablation. Using clinical EGMs, there was agreement in LAT differences found by DELTA, standard LAT annotation, and unipolar waveform cross-correlation. These results demonstrate an underlying relationship between a bipolar EGM’s peak amplitude and the activation time difference between its two electrodes. Our computational modeling and clinical results suggest this relationship can be leveraged clinically to improve measurement accuracy for small LAT differences, which may improve CV measurement at small spatial scales.